PENGUJIAN EFISIENSI PASAR BENTUK SETENGAH KUAT TERHADAP PERISTIWA PENGUMUMAN DIVIDEN TUNAI MENURUN DI BEJ - N. Agus Sunarjanto; L. Adisastra (Jurnal Keuangan dan Perbankan, 2008)
The Objective of this study was to examine the market efficiency of Jakarta StockExchange (JSX). Analyses of stock price and IHSG were gathered from 14 companies listed atJSX period 20042005 which shared lower dividend. Market model with t- test was used totest the hypothesis. The result of this study revealed that there was a significant abnormalreturn in t +1. It meant that lower cash dividend had information content which was shownby the quick responds of market, so the Jakarta Stock Exchange categorized it as half strengthmarket